Elucidating Biotransformation mechanisms of Extremophiles Assisted Emerging Contaminants (ECs) Degradation in Water under Extreme Conditions - Chia, Xing Kai (Curtin University, 2024)
Emerging contaminants (ECs) such as diclofenac, methylparaben and 1,2,4-triazole are widely detected in various water bodies, while conventional water and wastewater treatment methods are inefficient in removing ECs from water. Extremophiles are promising candidates in the removal of ECs due to their high resilience towards harsh and toxic environments. In this study, extremophiles were isolated from Miri region for the removal of 1,2,4-triazole, methylparaben and diclofenac under extreme conditions of low pH, high temperature and high salinity.